Identification of candidate AFLP markers and BAC clones for the fine molecular mapping of Tungro spherical virus resistance gene in rice (Oryza Sativa L.) - Panes, Vivian A. (2002)
Tungco disease that inflicts heavy losses on rice is caused by rice tungro spherical virus (RTSV) and rice tungro basilliform virus (RTBV). It is transmitted by the green leafhoppers (Nephotettix virescents Distans). In this study, genetic and physical mapping of the tungro spherical virus (RTSV) resistance gene was undertaken by delineating the R gene to a narrow region of chromosome 4 through the identification of candidate AFLP markers. The F2 and F3 populations from the cross between T1-11-8, a TN1 line with introgressed R gene from ARC11554, and a susceptible line R4-40/RCN13-19-94 were grown for DNA isolation and tungro phenotypic screening. Two hundred eighty six F3 families were evaluated for tungro reaction through ELISA after RTSV iniculation using the green leafhopper as vector. A bulked segregant analysis for amplified fragment length polymorphism (AFLP) was performed on the 16 highly resistant and 16 highly susceptible F2 plants that were identified based on the ELISA scores of their corresponding F3 families. The AFLP profile of the R and S pools, and the four parentals were compared in each of the forty pairs of Pst1 and Mse1 primers as well as forty pairs of EcoR1 and Mse1 primers used. AFLP analysis yielded seven polymorphic bands identified for Pst1/Mse1 primer combinations while five identified for the EcoR1 and Mse1 primer combinations. The genetic distance of 3.5 cM generated by the candidate AFLP markers was therefore closer to the RTSV resistance gene than the genetic distance of 5.5 cM generated using RAPD markers by Sebastian and co-workers (1996). Assuming that the clones are randomly distributed in the genome, therefore, the number of clones needed to complete a continuous overlapping contig is 127 and the probability of completing the contig is P=0.976 which is close to 1.0 (100%0. As part of the recommendations, confirmation of the candidate markers should be done by debulking the 16 bulked susceptible and 16 bulked resistant markers and running them in PAGE using the same primers that produced polymorphic bands. Further confirmation will also be conducted by running the 286 F2 DNAs in PAGE using the same primers in comparison to the parentals.
"May 2002."
Research project funded by University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Thesis (Ph.D. Biology)--University of the Philippines Diliman.
Keywords: Rice -- Diseases and pests; Gene mapping; Plant molecular genetics; Bacterial artificial chromosomes